Pelatihan Integrasi Teknologi dalam Pengembangan Bahan Ajar untuk Guru dan Kepala Sekolah Dasar: Implementasi Penggunaan Canva - Agustina, Dyan Widya; Restiawati, Yanti; Haryaka, Usfandi (Jurnal Pengabdian Ahmad Yani, 2024)
This community service program aims to integrate Canva, a popular graphic design platform, into educational settings with a focus on its impact on teaching practices, student engagement, and administrative support. Through training and workshops involving elementary school teachers and principals, this program explores the benefits, challenges, and strategies associated with using Canva to create visually appealing learning materials. The results show that Canva enhances teacher efficiency by streamlining the creation of modules, games, and worksheets, while also fostering student interest through colorful and interactive content. Challenges such as limited infrastructure and varying levels of teacher proficiency were identified, along with strategies to address them, including targeted training and collaborative learning initiatives. Principals emphasized the importance of recognizing and incentivizing proficient use of technology among teachers, as well as optimizing school resources to support effective integration of Canva. Overall, this community service program highlights the transformative potential of Canva in improving teaching practices and student engagement, while also underscoring the need for ongoing support and training to maximize its benefits.